Prevalence and Clinical Significance of Occult Fractures in the Extremities in Children - Ma, Qichao; Jiao, Qin; Wang, Shiqi; Dong, Liangchao; Wang, Yicheng; Chen, Mengjie; Wang, Sun; Ying, Hao; Zhao, Lihua (Frontiers in Pediatrics, 2020)
Objective: Diagnosis of occult fractures by initial plain radiographs remains challenging in children in the emergency room. This study was to assess the prevalence and distribution of occult fracture in children with acute extremities injuries (AEI) and clinical suspicion of fracture. Methods: We conducted a retrospective study to review the medical records of all pediatric patients with AEI in the orthopedic emergency room from January 1, 2017 to December 31, 2019. For patients with concerning history and physical examination but negative initial radiographs, we conducted the following three diagnostic strategies according to the choose of children’s parents: immediate MRI scanning, (2) immediate CT scanning, or (3) empiric cast immobilization with orthopedic follow-up radiographs at two weeks post-injury (late radiographs). Prevalence and distribution of occult fracture were recorded. Results: 43560 pediatric patients meet the inclusion criteria. A total of 4916 fractures of the extremities were confirmed by initial plain radiographs, and 550 occult fractures were confirmed by immediate MRI, immediate CT, or late radiographs. The prevalence of occult fracture in the extremities was 10.1% (550/5466). Supracondylar fractures were the most prevalent (2325/5466, 42.5%) but had the lowest rate of occult fractures (117/2325, 5.0%). The highest rate of occult fracture was distal epiphyseal fracture of the tibia and fibula (49/145, 33.8%) but these had a relatively lower prevalence of fractures (145/5466, 2.65%). Conclusions: We should be aware of the relative high prevalence of occult fractures in the extremities in children, especially when the injured site is in the high incidence area of occult fracture such as ankle.